Wartość krajobrazu w świetle cen terenów pod zabudowę w latach 1995-2000 - Łowicki, Damian (Wydawnictwo Ekonomia i Środowisko, 2010)
Research shows that transaction prices of building plots in the Poznań poviat vary according to the location and dependence on such local landscape elements as lakes and forests. It is an attempt to evaluate one of the landscape services and point out that lack of landscape harmony may generate economic consequence. The study uses data on transaction prices of plots for housing construction sold between1995 and 2000 in the Poznań poviat area. Using geostatistical methods, the time and spatial variability of plots prices was analysed. On this basis, further interpolation of these prices was carried out in the poviat area. The research shows that both the extend and level of impact of lakes and forests on plot prices are significant and may be expressed by means of a mathematical model.
Landscape value in relation to building land prices in the years 1995-2000
Keywords: ecosystem services; cultural and recreational services; building land prices; semivariogram and kriging; Poznań poviat